2005
DOI: 10.1002/chin.200518041
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Clean Oxidation of Alcohols with Benzimidazolium Fluorochromate (BIFC) under Solvent Free Conditions.

Abstract: Oxidation O 0212Selective and Clean Oxidation of Alcohols with Benzimidazolium Fluorochromate (BIFC) under Solvent Free Conditions. -Benzimidazolium fluorochromate is shown to be an efficient oxidant for primary or secondary alcohols. The corresponding aldehydes or ketones are formed in high yields. -(SIVAMURUGAN, V.; RAJKUMAR, G. A.; ARABINDOO, B.; MURUGESAN*, V.; Indian J. Chem., Sect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The heterocyclic aldehyde used was indole-2-aldehyde. BIFC was prepared by reported method 17 and its purity is checked by an iodometric method. Acetic acid was purified by standard method and the fraction distilling at 118 o C was collected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The heterocyclic aldehyde used was indole-2-aldehyde. BIFC was prepared by reported method 17 and its purity is checked by an iodometric method. Acetic acid was purified by standard method and the fraction distilling at 118 o C was collected.…”
Section: Methodsmentioning
confidence: 99%
“…A search of literature revealed that only few reports are available for kinetics of oxidation of heterocyclic aldehydes [13][14][15][16] . Benzimidazolium fluorochromate [17][18][19][20] was reported as a mild, stable and selective oxidant. BIFC has been reported as an effective oxidant for the oxidation of alcohols 17,18 , benzaldehydes 19 and anilines 20 .We have been interested in the kinetic and mechanistic aspects of the oxidation by complexed Cr(VI) species, and several studies on halochromates have already been reported [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidants ICC and BCC were prepared and characterized according to reported method 17,18 . All other chemicals used were of AnalaR grade.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, there is continued interest in the development of new Cr(VI) reagents for the effective and selective oxidation of organic substrates, under mild conditions, because Cr(VI) is established as a versatile oxidant for the oxidation of a variety of organic compounds 1 . Many Cr(VI) reagents like benzimidazolium fluorochromate 2 , tetrahexylammonium fluorochromate 3 , , quinolinium fluorochromate 6 and tetraethylammonium chlorochromate 7 have been studied in recent years for the oxidation of various organic substrates.…”
Section: Introductionmentioning
confidence: 99%